African Indigenous Medicine Activities in Mbarara Municipality, Uganda - Godfrey, Barigye (International Journal of Research in Sociology and Anthropology, 2019)
Some African indigenous medicine healers and neo-liberalists have misused the cherished objectives of community values and turned it into witch-craft characterized with human sacrifice, money extortion, and many more evil related practices. The study was on activities of traditional indigenous knowledge in Mbarara Municipality, Uganda. It was established that most African indigenous healers were mainly practicing herbalism, midwifery/traditional birth attendance, spirituality/foretelling, bone-setters, snake poison healers and rain-makers. The African indigenous healers were in the age group of 40 years and above, had an educational level of secondary, most of them were females, who were Banyankore, Baganda, Congolese and Swahili, and were married. Most of the beneficiaries of African indigenous medicine were farmers and Banyankore by tribe. It was concluded that African indigenous medicine practices and systems of local people are interactive technology whose dissemination is feasible, efficient, and cost-effective when learnt from village-level experts.